Progress on Waveguide-Integrated Graphene Optoelectronics - Jiaqi Wang; Zhenzhou Cheng; Xuejin Li (Advances in Condensed Matter Physics)
Graphene, a single layer of carbon atoms arranged in the form of hexagonal lattice, has many intriguing optical and electrical properties. However, due to the atomic layer thickness, light-matter interactions in the monolayer graphene are naturally weak when the light is normally incident to the material. To overcome this challenge, waveguide-integrated graphene optoelectronic devices have been proposed and demonstrated. In such coplanar configurations, the propagating light in the waveguide can significantly interact with the graphene layer integrated on the surface of the waveguide. The combination of photonic integrated circuits and graphene also enables the development of graphene devices by using silicon photonic technology, which greatly extends the scope of graphene’s application. Moreover, the waveguide-integrated graphene devices are fully CMOS-compatible, which makes it possible to achieve low-cost and high-density integration in the future. As a result, the area has been attracting more and more attention in recent years. In this paper, we introduce basic principles and research advances of waveguide-integrated graphene optoelectronics.